2013
DOI: 10.3791/50955
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Forelimb Function after Unilateral Cervical SCI using Novel Tasks: Limb Step-alternation, Postural Instability and Pasta Handling

Abstract: Cervical spinal cord injury (cSCI) can cause devastating neurological deficits, including impairment or loss of upper limb and hand function. A majority of the spinal cord injuries in humans occur at the cervical levels. Therefore, developing cervical injury models and developing relevant and sensitive behavioral tests is of great importance. Here we describe the use of a newly developed forelimb step-alternation test after cervical spinal cord injury in rats. In addition, we describe two behavioral tests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…As previously observed (Cannon et al, 2009b), the endpoint rotenone dosing paradigm induces rapid motor impairment as measured using a postural instability test (PIT; Woodlee et al, 2008; Khaing et al, 2013). Thus, it is not surprising that all rotenone-treated animals (LV-GFP/MuLV and LV-hDJ-1/MuLV) exhibited motor behavior deficits, as well as rapid weight loss, associated with rotenone-induced systemic toxicity and gastrointestinal neuropathology (Drolet et al, 2009) (Supplemental Figure 2).…”
Section: Discussionmentioning
confidence: 59%
“…As previously observed (Cannon et al, 2009b), the endpoint rotenone dosing paradigm induces rapid motor impairment as measured using a postural instability test (PIT; Woodlee et al, 2008; Khaing et al, 2013). Thus, it is not surprising that all rotenone-treated animals (LV-GFP/MuLV and LV-hDJ-1/MuLV) exhibited motor behavior deficits, as well as rapid weight loss, associated with rotenone-induced systemic toxicity and gastrointestinal neuropathology (Drolet et al, 2009) (Supplemental Figure 2).…”
Section: Discussionmentioning
confidence: 59%
“…We found that more than 50% of the untreated 6-OHDA-lesioned rats had a diminished ability to alternate their forelimbs, as shown through the forelimb function test (Figure 1A), which was ameliorated by pre and post-lesion treatment with OA. This is a relatively new test, originally shown to be a robust assessment of neurological deficits in cervical spinal cord injury (Khaing et al, 2013). The forelimb akinesia (step test), limb-use asymmetry (cylinder test) and open field tests (Figures 1A–D) have long been used in assessment of parkinsonism in rodents (Walsh and Cummins, 1976; Tillerson et al, 2001; Mabandla and Russell, 2010), and have been shown to be reliable measures of neurobehavioral deficits resulting from 6-OHDA neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Two weeks post-treatment, rats underwent a forelimb function test to ascertain their ability to alternate their forelimbs. All procedure were performed as described by Khaing et al (2013). Briefly, the animals were held on a table top in a forelimb-only bearing stance, with both their forelimbs touching the table top.…”
Section: Methodsmentioning
confidence: 99%
“…Between-experimenter variation was minimized by maintaining the same experimenter for tests involving handling, whereas two experimenters were used for observation tasks. Six behavioral tests were utilized to examine functional recovery following SCI and treatment: the pasta eating test [47,48,61], the cylinder paw preference test [45,61,62], the vibrissae-elicited forelimb placing test [45], the forelimb step-alternation test [47,48], the PIT [47,48], and the grooming test [63]. The latter three are described in the supplemental information (figures S2 and S4-S6 (stacks.iop.org/ JNE/15/025004/mmedia)).…”
Section: Behavioral Assessmentmentioning
confidence: 99%
“…Here we designed the hydrogel to promote differentiation of the transplanted cells. Established behavioral tests, including the postural instability test (PIT) [44], the vibrissae-elicited placing test [45], the cylinder paw placement test [45], the grooming test [46], and our recently published pasta eating test and step alternation test, were used [47,48]. These tests provided insight into the functional recovery of the animals by examining multiple motions as well as spontaneous and elicited behavior, which provides insight into the overall capabilities as well as the difficulty of use; if an animal can use their limb but chooses not to the ease of use is revealed.…”
Section: Introductionmentioning
confidence: 99%